University and Public Libraries in the Virtual World between Reality and Future Prospects - Khader , Ibrahim Khalil (Dirasat: Educational Sciences, 2020)
This study deals with the existence of libraries and their curators in the virtual world, which is open and available for all users of the internet. As a result of this, the development of both university and public libraries was described through shedding more light on the moves and reasons of logging on libraries in the virtual world, and the central projects of academic and public libraries. In addition, this study provides general guidelines for both curators and users owho work side by side in the virtual world. It also surveys the developments of university and public libraries, services offered by both of them, difficulties encountered in the virtual word, and the activities of librarians. The significance of this study lies in its attempt to identify the roles played by both public and university libraries in the virtual world. The researcher proposes that public and university libraries in the virtual environment should play an active role by updating their services and keeping up with the developments in this field.